2020
DOI: 10.3390/diagnostics11010016
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Root Dilatation in Taiwanese Patients with Mucopolysaccharidoses and the Long-Term Effects of Enzyme Replacement Therapy

Abstract: Background: Cardiovascular abnormalities have been observed in patients with mucopolysaccharidosis (MPS) of any type, with the most documented abnormalities being valvular regurgitation and stenosis and cardiac hypertrophy. Only a few studies have focused on aortic root dilatation and the long-term effects of enzyme replacement therapy (ERT) in these patients. Methods: We reviewed echocardiograms of 125 Taiwanese MPS patients (age range, 0.1 to 19.1 years; 11 with MPS I, 49 with MPS II, 25 with MPS III, 29 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Aortopathy is an emerging issue in adult MPS with the exact pathogenesis being unclear ( 77 ), but accumulation of GAGs have been implicated in increased vascular stiffness ( 78 ), aortic narrowing ( 2 ) and aortic root dilatation ( 77 , 79 ). In a cohort of 34 MPS I-VII patients 35.3% developed aortic dilation, with the highest prevalence in MPS IVA (62.5%) ( 79 ) and 66% ( 80 ). A further cohort study of 69 patients demonstrated a prevalence of aortic root dilatation in 39.1% with the highest prevalence in MPS I-H and little effect of ERT on aortopathy ( 81 ).…”
Section: Cardiovascular Evaluationmentioning
confidence: 98%
“…Aortopathy is an emerging issue in adult MPS with the exact pathogenesis being unclear ( 77 ), but accumulation of GAGs have been implicated in increased vascular stiffness ( 78 ), aortic narrowing ( 2 ) and aortic root dilatation ( 77 , 79 ). In a cohort of 34 MPS I-VII patients 35.3% developed aortic dilation, with the highest prevalence in MPS IVA (62.5%) ( 79 ) and 66% ( 80 ). A further cohort study of 69 patients demonstrated a prevalence of aortic root dilatation in 39.1% with the highest prevalence in MPS I-H and little effect of ERT on aortopathy ( 81 ).…”
Section: Cardiovascular Evaluationmentioning
confidence: 98%
“…Through our search, we gathered (at least) 47 patients reported with CVD (MVS, MVR, AVS, ARe), BR, AT, VSD, asymmetric SH and CH and arrhythmogenic RVHCM, which can result in cardiac arrest and recommendation for heart transplant [532,589,[604][605][606][607][608][609] (Table 6, Supplementary Tables S2 and S3). Additionally, we found eight studies with patients displaying cardiac involvement, but the subtype of Sanfilippo syndrome (A, B, C or D) was not specified, and thus they have not been included [512,540,544,556,564,591,600,610].…”
Section: Sgsh-lsdmentioning
confidence: 99%
“…Our systematic search identified (at least) 39 MPS-IIIB patients described with cardiac symptoms, including CVD (MVS, MVR, AVS, ARe), to BR, AT, VSD, SH (asymmetric), CH and arrhythmogenic RVHCM, which in some cases resulted in cardiac arrest and/or recommendation for heart transplant [589,[604][605][606]609,[612][613][614] (Table 6, Supplementary Tables S2 and S3). As mentioned in the previous paragraph, we found eight additional studies with MPS_III patients described with cardiac involvement, but the subtype was not specified, thus these studies have been excluded (Supplementary Table S3) [512,540,544,556,564,591,600,610].…”
Section: Sgsh-lsdmentioning
confidence: 99%
See 1 more Smart Citation
“…This degree of vascular fragility is not seen in IEM; however, recent studies have brought aortic root dilatation to light as an important complication of MPS and more specifically of MPS IVA (Morquio syndrome) [ 25 ]. Fabry-like stroke events are not present in EDS.…”
Section: The Clinical Presentation Of Eds An Overviewmentioning
confidence: 99%